a) "(ye^{2xy} + x) dx + (bxe^{2xy}) dy=dU", then "ye^{2xy}+x=\\frac{\\partial U}{\\partial x}" and "bxe^{2xy}=\\frac{\\partial U}{\\partial y}".
We have "\\frac{\\partial^2 U}{\\partial x\\partial y}=\\frac{\\partial^2 U}{\\partial y\\partial x}", that is "\\frac{\\partial}{\\partial x}(bxe^{2xy})=\\frac{\\partial}{\\partial y}(ye^{2xy}+x)"
"\\frac{\\partial}{\\partial x}(bxe^{2xy})=be^{2xy}+2bxye^{2xy}", "\\frac{\\partial}{\\partial y}(ye^{2xy}+x)=e^{2xy}+2xye^{2xy}" , so "be^{2xy}+2bxye^{2xy}=e^{2xy}+2xye^{2xy}", and we obtain "b=1".
Hence "\\frac{\\partial U}{\\partial y}=xe^{2xy}", so "U=\\frac{e^{2xy}}{2}+f(x)".
Then "\\frac{\\partial U}{\\partial x}=ye^{2xy}+f'(x)". Since "\\frac{\\partial U}{\\partial x}=ye^{2xy}+x", we have "f'(x)=x".
Let "f(x)=\\frac{x^2}{2}", then "U=\\frac{e^{2xy}+x^2}{2}"
So the given equation we can rewrite as "d\\left(\\frac{e^{2xy}+x^2}{2}\\right)=0", general solution of which is "\\frac{e^{2xy}+x^2}{2}=\\frac{C}{2}" or "e^{2xy}+x^2=C"
b)General solution we will look in form "y=y_1+u=u+\\sin x"
We have "y'=u'+\\cos x", then
"u'+\\cos x=\\frac{2\\cos^2x-\\sin^2x+(u+\\sin x)^2}{2cosx}"
After expanding brackets and moving "\\cos x" to the right side, we obtain
"u'=\\frac{u^2+2u\\sin x}{2cosx}" or "\\frac{du}{dx}=\\frac{u^2+2u\\sin x}{2cosx}"
So "2\\cos xdu=u^2dx+2u\\sin xdx" or "2\\cos xdu=u^2dx-2ud(\\cos x)"
Since "d(UV)=VdU+UdV" for every differentiable "U" and "V", we have "2d(u\\cos x)=u^2dx"
Let "u\\cos x=v", then "2dv=\\frac{v^2}{\\cos^2 x}dx".
So we have "v=0" or "\\frac{2dv}{v^2}=\\frac{dx}{\\cos^2 x}" or "-2d\\left(\\frac{1}{v}\\right)=d(\\tan x)" . We obtain the general solution "v=0" or "\\tan x+\\frac{2}{v}=C".
Reurning to "u", we obtain "u=0" or "\\tan x+\\frac{2}{u\\cos x}=C". And, returning to "y", we obtain "y=\\sin x" or "\\tan x+\\frac{2}{(y-\\sin x)\\cos x}=C". Expessing "y", we obtain "y=\\sin x" or "y=\\sin x+\\frac{2}{C\\cos x-\\sin x}"
Answer: a)"b=1", "e^{2xy}+x^2=C", b)"y=\\sin x" or "y=\\sin x+\\frac{2}{C\\cos x-\\sin x}"
Comments
Leave a comment